(untitled) (Heritage, 2022)
We can trace the development of notary on the eastern coast of the Adriatic and its hinterland since the 11th century. Since then, notaries had the right to issue documents in cities. In Istria, the note u appears for the first time in historical sources in 932 in Koper, and from 991 in Poreč. The documents issued by the notary had public faith (fides publicam) and were valid as evidence in court cases. At the end of the 12th century, the notary appeared in all Dalmatian cities as a very important institution. The notarial deed or instrument suppressed the map from public use. Notaries issued instruments, but at the request of the so-called rogatia (the act is called rogation, and the notary is rogatus, i.e. the petitioned notary). Rogatusje drew up a concept (sheda) at the request of the party, which he wrote in his notary book (liber imbeviaturarum or abbreviaturarum). After the rogation, and in at least three days, the notary had to issue the ispra, based on the entry he previously entered in his notary book (liber imbreviaturarum or ambreviaturarum). The issued document was certified by the notary with his signum notarii (monogram), which was written by hand below the text. The final document, certified, acquires public faith and becomes fidem publicam. In the Dalmatian cities, documents from the 13th century, in addition to the notary, had to be examined by the examiner (city clerk), who in southern Dalmatia are auditores. In Slavonia, since the 13th century, there were special institutions (loca credibilia) where documents were issued. These were usually chapters and monasteries. At the beginning of loca credibilia, seals were also issued on documents, and they were usually drawn up by the chamberlain lector. Later, the chamberlain lector had his own scribes or notaries to draw up documents. Loca credibilia also produced authentic copies of issued transumpta authentica documents, which were valid if the original was lost. In Slavonia there were known loca credibilia - in Zagreb, Požega, Čazma, Topusko, and in Dalmatia the chapters had their own loca credibilia: Kinina, Zadar, Skradin, Trogir and Vrana. Very early on, Dubrovnik had an office with lawyers and notaries trained in Italy. The people of Dubrovnik established their offices, next to Dubrovnik, from Albania to Hungary, where they went on trade trips. The people of Dubrovnik appointed heads of the office, who were called students, logothets, scribes or grammarians. Dubrovnik had a state office very early on with lawyers and notaries. Dubrovnik documents had, unlike other documents, a sanction and an oath - an anathema. The document was almost never signed or named by witnesses. The notary certainly played an extraordinary role in the area of ​​the eastern coast of the Adriatic and the hinterland in the Middle Ages. He left a positive legal mark in the general and legal medieval history of this area.